Dynamics of Apparent Horizons in Quantum Gravitational Collapse - Tavakoli, Yaser (2018)
We study the gravitational collapse of a massless scalar field within the effective scenario of loop quantum gravity. Classical singularity is avoided and replaced by a quantum bounce in this model. It is shown that, quantum gravity effects predict a threshold scale bellow which no horizon can form as the collapse evolves towards the bounce.